Policy and Systems Reform for Blended Learning: A Mixed-Methods Framework for Improving Assessment Performance in Teacher Education - Priya Nair Priya Nair (Educational Innovation and Learning Transformation, 2025)
Blended learning has emerged as a structurally significant modality in teacher education, combining face-to-face instruction with online components in ways that can expand pedagogical flexibility and accommodate the diverse professional schedules of pre-service and in-service teachers. Yet the proliferation of blended designs across teacher preparation programs has consistently outpaced the institutional capacity to implement them coherently, leaving persistent gaps between the learning outcomes that blended configurations promise and the assessment performance that programs reliably produce. This mixed-methods paper proposes a conceptual framework for policy and systems reform in blended teacher education that integrates evidence-based instructional design, accountability-oriented feedback structures, and equity-sensitive governance into a testable, scalable model. Drawing on the educational technology literature, self-regulation research, and implementation science, the framework identifies four interdependent reform levers: outcome-aligned instructional sequencing, actionable and timely feedback architecture, responsible learning analytics integration, and systemic policy conditions supporting sustainable adoption. A quasi-experimental evaluation design involving 155 pre-service teachers across two cohorts in a redesigned blended teacher education sequence provides the study architecture within which these levers operate. Synthetic outcome data are organized into three quantitative tables presenting engagement, performance, and satisfaction benchmarks alongside published effect-size estimates from comparable intervention studies. The paper argues that improving assessment performance in blended teacher education requires not incremental adjustment of individual course elements but coordinated systemic reform encompassing instructional design quality, learner support infrastructure, and the institutional policies that determine whether evidence-based practices can take root and persist across program cycles.